A manipulative interplay between positive and negative regulators of phytohormones: A way forward for improving drought tolerance in plants - Mubarik, Muhammad Salman; Khan, Sultan Habibullah; Sajjad, Muhammad; Raza, Ali; Hafeez, Muhammad Bilal; Yasmeen, Tahira; Rizwan, Muhammad; Ali, Shafaqat; Arif, Muhammad Saleem (Physiologia plantarum, 2021)
Among different abiotic stresses, drought stress is the leading cause of impaired plant growth and low productivity worldwide. It is therefore essential to understand the process of drought tolerance in plants and thus to enhance drought resistance. Accumulating evidence indicates that phytohormones are essential signaling molecules that regulate diverse processes of plant growth and development under drought stress. Plants can often respond to drought stress through a cascade of phytohormones signaling as a means of plant growth regulation. Understanding biosynthesis pathways and regulatory crosstalk involved in these vital compounds could pave the way for improving plant drought tolerance while maintaining overall plant health. In recent years, the identification of phytohormones related key regulatory genes and their manipulation through state‐of‐the‐art genome engineering tools have helped to improve drought tolerance plants. To date, several genes linked to phytohormones signaling networks, biosynthesis, and metabolism have been described as a promising contender for engineering drought tolerance. Recent advances in functional genomics have shown that enhanced expression of positive regulators involved in hormone biosynthesis could better equip plants against drought stress. Similarly, knocking down negative regulators of phytohormone biosynthesis can also be very effective to negate the negative effects of drought on plants. This review explained how manipulating positive and negative regulators of phytohormone signaling could be improvised to develop future crop varieties exhibiting higher drought tolerance. In addition, we also discuss the role of a promising genome editing tool, CRISPR/Cas9, on phytohormone mediated plant growth regulation for tackling drought stress.